2017
DOI: 10.1111/1756-185x.13231
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcome of lymphoma patients with pre‐existing autoimmune diseases

Abstract: Aims: Previous epidemiological studies have shown that autoimmune diseases increase the risk of lymphoma development. However, whether autoimmune diseases deteriorate the outcomes for lymphoma patients remains unclear. This study aimed to identify the clinical features of lymphoma patients with pre-existing autoimmune diseases. Whether pre-existing autoimmune diseases impacted progression-free survival (PFS) and overall survival (OS) in lymphoma patients was further investigated. Methods:We retrospectively rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Our study and other previous studies have involved too small numbers of patients with SLE to be able to confirm these findings. The study by Shih et al reported comparable outcomes in NHL patients (53% had DLBCL) with and without pre-existing AID [40]. This study was based on few cases with DLBCL and AID and reported only outcomes for the whole AID group together.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our study and other previous studies have involved too small numbers of patients with SLE to be able to confirm these findings. The study by Shih et al reported comparable outcomes in NHL patients (53% had DLBCL) with and without pre-existing AID [40]. This study was based on few cases with DLBCL and AID and reported only outcomes for the whole AID group together.…”
Section: Discussionmentioning
confidence: 94%
“…In one study using the Surveillance, Epidemiology, and End Results (SEER)-Medicarelinked database B-cell mediated AID was listed in 4.5% of almost 6000 patients registered with a DLBCL diagnosis at the age of 66 years [29]. One study reviewing medical records of 913 newly diagnosed lymphoma patients found AID prior to lymphoma diagnosis in 34 of the patients (3.7%) and of these 18 patients had DLBCL [40]. However, the definition of eligible AID diagnoses is not clear in the last two studies and may be different from the definition we have used.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a study using the Nebraska Lymphoma Study Group and the Mayo Clinic Lymphoma Database registries of 1595 NHL patients found that RA was associated with improved NHL-related outcomes, with a 40% reduced risk of death and a 60% lower risk of lymphoma relapse or progression compared with non-RA NHL patients; however, patients with concomitant RA and NHL were more than twice as likely to die from causes unrelated to lymphoma 20 . A study in Taiwan retrospectively reviewed 913 medical records of newly diagnosed lymphoma patients and found that pre-existing autoimmune diseases, which included B-cell- and T-cell-mediated autoimmune diseases, and other thyroid autoimmune diseases, were not associated with inferior progression-free survival or OS 22 . A study using the SEER database with 5926 DLBCL patients, examined survival patterns in DLBCL cases with RA, SLE, SS, and other B-cell-mediated autoimmune diseases, and found no significant difference compared to patients with no history of these diseases 23 .…”
Section: Discussionmentioning
confidence: 99%
“…2,5,6 The data on disease outcomes in lymphoma patients who have preexisting autoimmune conditions is limited. A recent study by Shih et al 7 observed a comparable progression-free survival (PFS) and OS between lymphoma patients with or without autoimmune diseases.…”
mentioning
confidence: 99%
“…The pathophysiology of PCMZL remains unclear. 7 It is thought to be driven by chronic immune responses to pathogens or auto-antigens. 2,5,8 Treatment of PCMZL in SLE patients does not differ from that administered to patients without SLE 8 While regression of localized PCMZL associated with microbial pathogens can be achieved with antibiotic therapy, persistent infection or resistant lymphoma may require conventional oncologic modalities.…”
mentioning
confidence: 99%